Geomoprhological and sedimentological characteristics of Nestos river, active delta, after the construction of the dams - Γαρέζος, A.; Αλμπανάκης, Κ. (Bulletin of the Geological Society of Greece, 2011)
The purpose of this paper is the geomorphological and sedimentological study of modern Nestos River Delta, to examine the effect of the dams to the sedimentological regime of the coastal zone. Nestos Delta suffered a series of anthropogenic influences; the most significant was the channeliza-tion of the river bed, which prevents avulsion and enforces the river to discharge to the sea with one main channel. A DGPS with accuracy better than 1m (GMS-2- Topcon), was used for mapping the coastline, along with sampling the coastal sediments. Sedimentological analysis revealed that the mean size of the sandy material of the coastline reduces with increasing the eastward distance from the river mouth. The western coastline revealed a more complex situation, since it had inherited characteristics from older, abandoned river mouths, bars, spits etc, existed prior to anthropogenic influence. Comparison between the DGPS survey and the 1970 topographic maps revealed some areas with erosional and some with depositional tendencies. A clear erosional tendency was not rec-orded. Furthermore comparison, between 2000 GPS survey, and the present 2009 DGPS survey, recorded a stability of the coastline within the resolution and the accuracy of the instruments. A pos-sible explanation, is the dramatic reduction of the active area of the delta, due to anthropogenic influ-ence, where at its natural stage, was dispersing sediments with avulsion and multiple river channels in an area of 500 km2, but now the active area, where deposition is possible, is only 45.84 km2.